SISTEM BAGI HASIL USAHA FATTENING SAPI PERSPEKTIF EKONOMI ISLAM DI DESA SUKASARI, KECAMATAN AIR PERIUKAN, KABUPATEN SELUMA - Rehan Nur Kholis (JSE: Jurnal Sharia Economica, 2025)
This study aims to determine the profit-sharing system in a cattle Fattening business in Sukasari Village, Air Periukan District, Seluma Regency, and to determine the cattle Fattening system from an Islamic economic perspective. The research method used in this study is qualitative research. The informants who will become the subjects of this study are cattle owners and cattle breeders. Data collection techniques used include observation, interviews, and documentation. Data analysis in this study was conducted qualitatively by describing the overall results. The results of this study indicate that the profit-sharing system in the cattle Fattening business in Sukasari Village can be considered an adaptive, efficient, and sustainable business model. The cattle Fattening system in Sukasari Village complies with Islamic economic principles, both in terms of the contract, the absence of prohibited elements, the application of the value of ihsan (charity), and its contribution to the economic and social well-being of the community.